A deeper shade of green: inspiring sustainable drug manufacturing. Issue 1 (22nd November 2016) - Roschangar, Frank; Colberg, Juan; Dunn, Peter J.; Gallou, Fabrice; Hayler, John D.; Koenig, Stefan G.; Kopach, Michael E.; Leahy, David K.; Mergelsberg, Ingrid; Tucker, John L.; Sheldon, Roger A.; Senanayake, Chris H.
Abstract : Green and sustainable drug manufacturing goes hand in hand with forward-looking visions seeking to balance the long-term sustainability of business, society, and the environment. Abstract : Green and sustainable drug manufacturing go hand in hand with forward-looking visions seeking to balance the long-term sustainability of business, society, and the environment. However, a lack of harmonization among available metrics has inhibited opportunities for green chemistry in industry. Moreover, inconsistent starting points for analysis and neglected complexities for diverse manufacturing processes have made developing objective goals a challenge. Herein we put forward a practical strategy to overcome these barriers using data from in-depth analysis of 46 drug manufacturing processes from nine large pharmaceutical firms, and propose the Green Aspiration Level as metric of choice to enable the critically needed consistency in smart green manufacturing goals. In addition, we quantify the importance of green chemistry in the often overlooked, yet enormously impactful, outsourced portion of the supply chain, and introduce the Green Scorecard as a value added sustainability communication tool.